Los ejemplares de Cercopoidea (Hemiptera: Auchenorrhyncha) depositados en la colección entomológica del Instituto Fundación Miguel Lillo, Tucumán, Argentina - Foieri, Álvaro (2015)
The 2,903 specimens of Cercopoidea (Hemiptera: Auchenorrhyncha) housed in the collection of the Instituto Fundacion Miguel Lillo (Tucumán, Argentina) were examined. The specimens belong to 33 species in 14 genera and 3 families, Aphrophoridae, Cercopidae y Clastopteridae. For each taxon, complete information about original publication, synonymic list, collection data, condition and additional information is given. The present catalogue is published in compliance with recommendation 72 F.4 of the International Code of Zoological Nomenclature.